Representações sociais da aposentadoria : um estudo com docentes e ex-docentes universitários - Nóbrega, Cléverson Vasconcelos da (2017)
The purpose of this thesis is to understand how the social representations of retirement are configured among teachers and former university teachers who go through the period of transition to retirement between the pre-retirement and post-retirement periods. For this, the Theory of Social Representations (TRS), conceived by the social psychologist Serge Moscovici in 1961, adopted as a theoretical-conceptual contribution that advocates a link between the psychological and the social, based on the inseparability between the subject, object and society. The study is justified by the fact that a demographic transition occurs in Brazil, whose situation brings with it a de-institutionalization of the life course, with changes in the family structure, (re) signification of old age, changes in the market with the postponement of the exit of individuals from this market and, in general, a rupture in the traditional form of retirement, with the possibility of returning to work. In this context, the apprehension of the retirement process of university professors and former university teachers requires a multidimensional view of the phenomenon, based on the observation of individual (micro), family and organizational (meso) as well as social, cultural, political and economic aspects (macro), to the detriment of a merely punctual vision. Methodologically, this is a qualitative approach supported by two case studies, carried out in sequence, being first in Lisbon-Portugal and the second in João Pessoa-PB, both characterized by documentary research preceded by interviews. In the first documentary survey, carried out in the Correio da Manhã newspaper, the retiree represented as morally and financially fragile, possibly due to the economic crisis that hit Portugal during the period studied (2010-2015). In the two newspapers selected for research in the Northeast (Jornal do Commercio and Correio da Paraíba), the retiree is concerned about his health and well-being, but most of the time, he is also fragile, vulnerable and indebted. It has retirement as a frustrating regret, perhaps because, even though it is aware of its rights, it feels powerless to try to guarantee them, given the limited capacity for political articulation that translates into a discriminatory feeling, for the difference of rights between active and "inactive". As in Portugal, Brazil's unfavorable economic conditions, represented in the newspapers as result of the pension deficit, suggest that the retired figure is a big villain and "guilty" of the debt. On the Portuguese surveyed, it observed that retirement is often clothed with subtleties and seen as taboo, caused by isolation approaching a kind of social death. The social representations related to retirement in the narratives of the subjects, some can be highlighted: a) pecuniary allowance - although this benefit is a motivator to delay the application for retirement, is not the most relevant, given the possibility of continuity of work outside the gym; b) domestic activities - teachers, in general, are able to cope more naturally with teachers than the arrival of retirement because they commonly accumulate household responsibilities; c) age - it is possible to perceive some prejudice or distance between peers in the institution, caused by the older age of some, suggesting a lack of knowledge updating, possibly due to physical and / or mental fatigue; d) this distancing can also be fueled by the lack of recognition of the younger ones in relation to the older ones, aspect mentioned in the research by the two groups interviewed, annoying the retirees who still feel they can contribute to the institution. The heterogeneity of the social representations obtained between UFPB teachers and former teachers reveals that the retirement process felt in different ways, reinforcing the understanding of its complex and unique character.